2015
DOI: 10.1039/c4nr06348a
|View full text |Cite
|
Sign up to set email alerts
|

Cylindrical nanostructured MoS2 directly grown on CNT composites for lithium-ion batteries

Abstract: Direct attachment of MoS2 to materials with carbonaceous architecture remains a major challenge because of non-intimate contact between the carbonaceous materials and active MoS2 material. In this study, we report a new unique synthetic method to produce a new type of hybrid nanostructure of MoS2-CNTs composites. We developed a novel strategy for the synthesis of cylindrical MoS2 directly grown on CNT composites without the use of any other additives, exhibiting superior electrochemical performance as the anod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
73
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(76 citation statements)
references
References 39 publications
2
73
0
1
Order By: Relevance
“…The corresponding rate capability is shown in Figure 4c, where the capacity increases from 822 mAh g −1 to 984 mAh g −1 at 200 mA g −1 after 10 cycles and the capacity is maintained at 670 mAh g −1 at 1600 mA g −1 . The good electrochemical performances of MoS 2 ‐CNT composite are ascribed to the synergistic effects between the cylindrical nanostructured MoS 2 materials and CNT, and the prevention of aggregation by the unique structure and the high‐conductivity of CNT to improve the conductivity of insulating MoS 2 materials for LIBs 77. A similar strategy was applied by Srivastava and co‐workers and different weight ratios of MoS 2 and CNT (3:1 to 1:2) were discussed andenhanced electrochemical performances are demonstrated 78.…”
Section: Energy Storage Device Applicationsmentioning
confidence: 99%
“…The corresponding rate capability is shown in Figure 4c, where the capacity increases from 822 mAh g −1 to 984 mAh g −1 at 200 mA g −1 after 10 cycles and the capacity is maintained at 670 mAh g −1 at 1600 mA g −1 . The good electrochemical performances of MoS 2 ‐CNT composite are ascribed to the synergistic effects between the cylindrical nanostructured MoS 2 materials and CNT, and the prevention of aggregation by the unique structure and the high‐conductivity of CNT to improve the conductivity of insulating MoS 2 materials for LIBs 77. A similar strategy was applied by Srivastava and co‐workers and different weight ratios of MoS 2 and CNT (3:1 to 1:2) were discussed andenhanced electrochemical performances are demonstrated 78.…”
Section: Energy Storage Device Applicationsmentioning
confidence: 99%
“…MoS 2 has been well studied as a high capacity electrode material, achieving up to 1290 mAh g −1 when cycled with Li-ions to 0 V versus Li/Li + [ 29,30 ] and 854 mAh g −1 when cycled with Naions to 0 V versus Na/Na + . [ 31 ] In situ X-ray diffraction combined with Fourier Transform Infrared Spectroscopy (FTIR) spectroscopy has revealed that when MoS 2 is cycled to these very low potentials to achieve these very high capacities, molybdenum metal nanoparticles are formed within a Li 2 S matrix, and subsequent electrochemical cycling operates as a lithium-sulfur redox couple.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11][12] Aer graphene, the rst family member of these 2D nanomaterials, a number of other such nanomaterials have been discovered including phosphorene, silicene and transition metal dichalcogenides (TMDCs). 13 Among them, the TMDCs, such as WS 2 , MoS 2 , WSe 2 , exhibit a considerably high structural stability, with a melting point reaching up to 1185 C. They have been explored for applications in eld-effect transistors, 14 lithium-ion batteries, 15,16 integrated circuits, 17 gas sensors, 18 hydrogen evolution 19 and phototransistors.…”
Section: Introductionmentioning
confidence: 99%